Furanocoumarins from the twigs of Ficus chlamydocarpa (Moraceae). (February 2022) - Wandji, Nadine Tseme; Bitchagno, G. Thierry Mbahbou; Tchamgoue, Joseph; Stammler, Hans-Georg; Frese, Marcel; Lenta, Bruno Ndjakou; Sewald, Norbert; Fogue Kouam, Simeon
Graphical abstract: Highlights: Two furanocoumarin derivatives were isolated from Ficus chlamydocarpa . The structures were elucidated based on chemical and spectroscopic data. The new compound, 3-methoxypsoralen showed moderate antibacterial activity against Bacillus subtilis and Micrococcus luteus . Abstract: Two furanocoumarin derivatives, 3-methoxypsoralen (1 ) and 3, 5-dimethoxypsoralen (2 ), along with nine known compounds, friedelinol (3 ), 3-oxo-11 β -hydroxyoleanan-12-ene (4 ), lupeol (5 ), taraxer-3-one (6 ), a mixture of β -sitosterone (7a ) and stigmast-4, 22-dien-3-one (7b ), ergosterol (8 ), 9, 19-cyclolanost-3-one-24, 25-diol (9 ), oleanan-12-ene-3, 11-dione (10 ), and β -sitosterol 3- O - β -D-glucopyranoside (11 ) were isolated from the twigs of Ficus chlamydocarpa . Their structures were established by NMR spectroscopic analyses and HRESIMS. The structure of 1 was further confirmed from its single crystal X-ray diffraction. The crude extract, fractions and some isolated compounds were assessed for their preliminary antibacterial activity and cytotoxicity. One of the fractions (FB-B3) exhibited inhibition against the bacterial strain Pseudomonas agarici and induced a remarkable cytotoxic activity toward the human cervix carcinoma cell line KB-3-1 (IC50 0.166 mg/mL), and compounds 1, 6, and 7 showed moderate antibacterial activity against Bacillus subtilis and Micrococcus luteus .